Characterization of the promising poly(3-hydroxybutyrate) producing halophilic bacterium Halomonas halophila. (May 2018) - Kucera, Dan; Pernicová, Iva; Kovalcik, Adriana; Koller, Martin; Mullerova, Lucie; Sedlacek, Petr; Mravec, Filip; Nebesarova, Jana; Kalina, Michal; Marova, Ivana; Krzyzanek, Vladislav; Obruca, Stanislav
Highlights: Halomonas halophila was identified as auspicious halophilic PHA producer. Morphology and cell diameters depends on PHA content. Properties of produced materials can be tailored by manipulating NaCl concentration. Bacterium can produce PHA from various inexpensive and waste resources. Abstract: This work explores molecular, morphological as well as biotechnological features of the highly promising polyhydroxyalkanoates (PHA) producer Halomonas halophila . Unlike many other halophiles, this bacterium does not require expensive complex media components and it is capable to accumulate high intracellular poly(3-hydroxybutyrate) (PHB) fractions up to 82% of cell dry mass. Most remarkably, regulating the concentration of NaCl apart from PHB yields influences also the polymer's molecular mass and polydispersity. The bacterium metabolizes various carbohydrates including sugars predominant in lignocelluloses and other inexpensive substrates. Therefore, the bacterium was employed for PHB production on hydrolysates of cheese whey, spent coffee grounds, sawdust and corn stover, which were hydrolyzed by HCl; required salinity of cultivation media was set up during neutralization by NaOH. The bacterium was capable to use all the tested hydrolysates as well as sugar beet molasses for PHB biosynthesis, indicating its potential for industrial PHB production.